THE EFFECTIVENESS OF OCCUPATIONAL SAFETY AND HEALTH ON EMPLOYEES’ SAFETY IN MANUFACTURING FIRMS AT PENANG, MALAYSIA - MD AMIN, BOKHORI (International Journal of Multidisciplinary Research and Studies, 2021)
This study evaluated the relationship between occupational safety and health effectiveness on employees' safety in manufacturing firms in Penang, Malaysia. A sample size of 222 respondents was taken from 28 electrical manufacturing firms with a 6322 population and 361 samples to examine the relationship. A questionnaire was designed for data collection to measure safety and health procedures, safety and health policies, and work hazards and risk control on employees' safety in manufacturing firms. A stratified sampling method was used, and the data was analyzed using SmartPls 3.7.8. The study showed that safety and health procedures, safety and health policies, and work hazards and risk control have a significant relationship with employees' safety in manufacturing firms. However, the limitation of this study only covers electrical manufacturing firms. Suggested for future study focus on electronic, plastic, and fabricated manufacturing firms to be more effective in improving manufacturing firms' learning and development practices.